CRITERIA FOR RECEIVING DIRECT CASH TRANSFERS USING THE TOPSIS METHOD - Sari, Adek Kumala; Putri, Rezza Olga Shaponda; Willana, Rini Ade; Hazizah, Salsabillah (Journal of Mathematics and Scientific Computing With Applications, 2021)
In carrying out the direct cash transfer program during the Covid-19 pandemic, this is one of the efforts of the government to overcome poverty in Indonesia. In this case, it is very important that the assistance provided is right on target, so that it can be used by people in need. The method used in this research is the topsis method, by using the topsis method it is expected that the results given will find an alternative solution that is more precise and accurate because the calculation is based on predetermined criteria and weight values. Therefore, the researcher took the Topsis model for this study in order to provide maximum and accurate results.